2014
DOI: 10.1111/1541-4337.12093
|View full text |Cite
|
Sign up to set email alerts
|

Spoilage by Alicyclobacillus Bacteria in Juice and Beverage Products: Chemical, Physical, and Combined Control Methods

Abstract: Alicyclobacillus is a genus of spoilage bacteria causing contamination of juices and other beverage products that cannot easily be contaminated by other microbes because of their high acid contents. During the last 4 decades since the first species of Alicyclobacillus was isolated in 1967, Alicyclobacillus has become a major concern to the global juice and beverage industries, and many promising methods have been developed and applied to control them. After introducing the history and general characteristics o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(41 citation statements)
references
References 160 publications
1
37
0
1
Order By: Relevance
“…Many of the major bacterial groups observed in this dataset are commonly isolated from aquatic and terrestrial sources, and are therefore expected to be environmentally derived in both herbivorous and carnivorous species. Alicyclobacillus, Methylobacterium, Acinetobacter, and Agrobacterium represent some of the most abundant bacterial genera in our dataset, and all are common in soil and leaf surfaces (Vorholt, 2012; Kovaleva et al, 2014; Tianli et al, 2014). …”
Section: Discussionmentioning
confidence: 99%
“…Many of the major bacterial groups observed in this dataset are commonly isolated from aquatic and terrestrial sources, and are therefore expected to be environmentally derived in both herbivorous and carnivorous species. Alicyclobacillus, Methylobacterium, Acinetobacter, and Agrobacterium represent some of the most abundant bacterial genera in our dataset, and all are common in soil and leaf surfaces (Vorholt, 2012; Kovaleva et al, 2014; Tianli et al, 2014). …”
Section: Discussionmentioning
confidence: 99%
“…Perishable foods are often attacked by different microorganisms. The growth of most microorganisms can be prevented or lingered by adjusting storage temperature, reducing water activity, lowering pH, using preservatives, and using proper packaging [28].…”
Section: Microbial Spoilagementioning
confidence: 99%
“…The characteristic of the spoilage is the formation of a distinct antiseptic or medicinal off‐odour caused by guaiacol and the halophenols, including 2, 6‐dichlorophenol and 2, 6‐dibromophenol, and guaiacol is the mainly metabolite, which can be detected at a level of 2 μg L −1 by sensory means in fruit juices (Wang et al ., ; Cai et al ., ). It has been reported that Alicyclobacillus acidoterrestris had been isolated from various fruit juices, such as apple, kiwi, pear, grapefruit, lemon, orange, pear, passion, mango and so on, with apple is the most frequent isolation sources (Cai et al ., 2015a; Tianli et al ., ). Therefore, A. acidoterrestris have been always a major issue in the fruit juice industry and effective control methods are needed to minimise the risk of Alicyclobacillus ‐related spoilage.…”
Section: Introductionmentioning
confidence: 97%